PENGGUNAAN MEDIA WAYANG UNTUK MENGENALKAN KETELADANAN WALI SANGA DALAM PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Umi Farkhatun (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
This research is motivated by a sense of concern about the rise of phenomena that indicate a moral crisis and exemplary behavior among students, especially elementary school students. To overcome this, it is necessary to know effective learning media in learning in schools, especially in the subjects of Islamic Religious Education and Characteristics about the role models. This study aims to determine the effectiveness of the use of puppet media in learning the story of the examplary of Wali Sanga. The subjects were 23students from grade IV MI Dharwata Sikampuh Kroya. The method uses descriptive qualitative. The results showed that puppet media was effectively used in the learning of Islamic Religious Education and Characteristics for the theme of exemplary Wali Sanga characters as evidenced by the creation of a conducive learning climate and student assessment results that reached KKM by 78% and the achievement of basic competencies in Islamic Religious and Characteristics classes IV SD and MI.